Interregnum : Beyond Liquid Modernity - Bordoni, Carlo (Bielefeld : transcript-Verlag, 2016)
Challenging the thought of Zygmunt Bauman on the subject of liquid modernity, where everything has become unstable, precarious and uncertain, Carlo Bordoni (author with Bauman of State of Crisis) proposes to look at contemporary society as an interregnum, a temporary break with the past. In a condition characterised by anomie, the questioning of democratic achievements and the primacy of an unbridled economy, he offers a new perspective on our social condition. Understanding the interregnum and being aware of its instability and the social degradation that it entails can help us to make the right choices.
Frontmatter -- Table of content -- Preface -- I. Why we cannot define ourselves as modern -- II. The return of the subject -- III. A matter of class -- IV. The lost community -- References -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Class; Diagnosis of Our Time; Liquid Modernity; Mass Society; Social Inequality; Society; Sociological Theory; Zygmunt Bauman; SOCIAL SCIENCE / Sociology / General